Cofilin peptide homologs interfere with immunological synapse formation and T cell activation - Eibert, Sybille M.; Lee, Kyeong-Hee; Pipkorn, Rüdiger; Sester, Urban; Wabnitz, Guido H.; Giese, Thomas; Meuer, Stefan; Samstag, Yvonne (Proceedings of the National Academy of Sciences of the United States of America, 2004)
The formation of supramolecular activation clusters within the immunological synapse, crucial for sustained signaling and T lymphocyte activation, requires costimulation-dependent reorganization of the actin cytoskeleton. Here we have identified the actin-remodeling protein cofilin as a key player in this process. Cell-permeable peptides that block costimulation-induced cofilin/F-actin interactions in untransformed human T lymphocytes impair receptor capping and immunological synapse formation at the interface between T cells and antigen-presenting cells. As a consequence, T cell activation, as measured by cytokine production and proliferation, is inhibited.
Gesehen am 22.02.2021